2018
DOI: 10.1080/14786419.2018.1495637
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil and fractions isolated of Laurel to control adults and larvae of cattle ticks

Abstract: This study, was to evaluate the acaricidal effect of the essential oil (EO) and fractions (FR) obtained from Laurus nobilis leaves on Rhipicephalus (Boophilus) microplus. Eight fractions were obtained, however FR1: sabinene (37.83%), β-pinene (13.50%), 1,8-cineole (12.66%), α-pinene (12.56%) and FR8: α-terpineol (79.19%) were highlighted as to the larvicidal potential when submitted by Larval Packet Test. The EO was tested by the Adult Immersion Test, at concentrations of 200.00; 100.00 and 50.00 µL/mL caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The compound showed a parasite recovery rate of 43.18 %. In another study by Fernandez et al, Terpinen-4-ol,1, 8-cineole and linalool were found to present larvicidal activity against R. microplus larvae [48].…”
Section: Effect Of Essential Oil On Various Life Cycles Of C Elegansmentioning
confidence: 87%
“…The compound showed a parasite recovery rate of 43.18 %. In another study by Fernandez et al, Terpinen-4-ol,1, 8-cineole and linalool were found to present larvicidal activity against R. microplus larvae [48].…”
Section: Effect Of Essential Oil On Various Life Cycles Of C Elegansmentioning
confidence: 87%
“…Treatment with essential oils from some plants can affect tick mortality, fecundity, and egg hatching rate [ 122 ]. Recent studies examined the potential use of essential oils of Laurus nobilis (laurel) [ 162 ], Ocotea odorifera (canela sassafras) [ 163 ], Chrysopogon zizanioides [ 164 ], and Schinus molle [ 165 ] with levels of control between 7.59% to 99%, depending on the concentration of essential oil, tick life stage, and species. The combination of essential oils appears to enhance the effect of individual oils [ 166 , 167 ].…”
Section: Plant-derived Compounds With Potential Use For Tick Pest mentioning
confidence: 99%
“…The fact that Laurus nobilis plant displays biological activity sets it apart the most from plant others (Begum et al, 2013). It is associated with its extract and essential oils as an antifungal agent (Caputo et al, 2017), an antiviral agent, an antibacterial agent (Simić et al, 2004), an acaricidal agent (Sırıken et al, 2018) and an insecticidal agent (Fernandez et al, 2020). Knowledge of the disposal methods for helminths infected by plant extracts in laboratory animals is essential because parasites may act as variables affecting experimental outcomes.…”
Section: Introductionmentioning
confidence: 99%